Modifikasi Jubah Tembus Pandang Militer Dengan Memanfaatkan Material Kristal Anisotropik (Kalsit [CaCO3]) - Talalu, Lidya Ananda; Sianipar, Alexcandro Hibertus; Aritonang, Sovian (Fakultas Teknik UMSU, 2025)
The need for camouflage technology in the military is becoming increasingly urgent due to advancements in technology. Particularly in disguise operations, more sophisticated efforts are required to assist military personnel. Replacing facial camouflage gel with cloaks is considered more efficient as it can cover larger portions of soldiers' bodies. Therefore, an invisible cloak is developed utilizing anisotropic crystal materials, specifically calcite crystals (CaCO3), which work through light reflection to make the cloak's wearer appear invisible when light reflects off the cloak. With the help of transformational optics, this invisible cloak operates by bending the light wave paths around the object to be concealed.